Contexto de expertise e localização influenciando a gerência de TI - Lôbo, Jaziel Souza (2011)
The modern organizations are becoming increasingly dependent on Information Technology (IT), which requires implementation of an effective management support on this area where the high investments achieved can add value for the companies. The intent of reducing the damage caused by unusual computer problems is to provide an active and complete technical assistance to the users. This support team, which is responsible for IT maintenance, was initially named help desk and later, it was modified to service desk due to its significance and the integrated services that were added in this work area. The high diversity of hardware and software besides the current user s demand, which increase the complexity of the technical assistance, creates a new request: the human resource allocation that provides an appropriate profile for solving different types of computers problems. Professionals, who don t have the proper expertise (work experience and practice) for specific maintenance, can bring unnecessary travel for the technician and work inactivity for the requester.This paper aims the adjustment of a service desk tool developed at the Federal University of Santa Maria. The remodelling involves a context-aware computing, location awareness and temporal context characteristics and the technician expertise. The main results demonstrate a service desk context-aware system (sdvpc-SC), that also enables its access through a mobile device and the improvement of technical calls distributed by expertise and geographical location. The tests proved that the system is technically possible and its adjustments can be easily implemented in different types systems of the same category.